Evidencing the presence of merkel cell polyomavirus in papillary thyroid cancer - Monir Ghanghareh (Nature Portfolio, 2021)
Abstract Merkel cell polyomavirus (MCPyV) infects most people asymptomatically, but recent reports indicate that the virus may be related to carcinogenesis. This study aimed to evaluate the impact of MCPyV on the development of papillary thyroid cancer (PTC). Totally, 1057 samples, including 412 fresh biopsy samples (FBS) and 645 paraffin-embedded PTC biopsy samples (PEBS), and 1057 adjacent non-cancerous samples were assessed for the presence of MCPyV DNA and RNA. MCPyV DNA was positive in 215 (20.3%) of samples, including 126 (30.6%) in FBS and 89 (13.8%) in PEBS. In MCPyV-positive samples, the mean MCPyV copy number was higher in the patients with FBS (2.3 × 10–1 ± 0.5 × 10–1 copies/cell) compared to PEBS (0.7 × 10–4 ± 0.1 × 10–4 copies/cell) and adjacent non-PTC normal samples (0.3 × 10–5 ± 0.02 × 10–5 copies/cell), indicating a statistically significant difference (P < 0.001). The LT-Ag RNA expression was higher in FBS compared to PEBS, while VP1 gene transcript was not detected in any samples. Although our findings showed the presence of MCPyV in a subset of PTC Iranian patients, further research is required to confirm these findings.